Degradable composite material and application of degraded fiber thereof in BMC (bulk molding compound) process
By using degradable epoxy resin composition and raw material fibers to prepare composite materials, and applying degraded fibers in the BMC process, the problem of difficult degradation and reuse of existing BMC thermosetting plastics is solved, and the degradability and reusability of composite materials is achieved.
Patent Information
- Application Number
- CN202411656133.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
The existing BMC thermosetting plastics are difficult to degrade and reuse, resulting in high environmental pressure. The need to develop a degradable and reusable composite material to achieve carbon neutrality benefits.
The composite material is prepared by using degradable epoxy resin composition and raw material fibers. The degradable epoxy resin is modified to improve the degradation performance, and the degraded fibers are used for pre-reaction in the BMC process to achieve the reuse of the composite material.
It achieves good degradation and mechanical properties of composite materials, and can be applied in BMC processes. After degradation, the fibers can be recycled and reused, effectively avoiding the impact of post-treatment of composite materials on the environment.
Smart Images

Figure BDA0005142156540000061
Abstract
Description
Technical Field
[0001] The invention relates to C08L and the field of polymer compounds, and in particular to an application of a degradable composite material and degraded fibers thereof in a BMC process. Background Art
[0002] BMC (bulk molding compound) is a thermosetting plastic that is mixed with an inert filler to form an adhesive "putty-like" composite material for compression molding or injection molding. The composite material has good flame retardancy and anti-tracking properties, high dielectric strength, good corrosion resistance and stain resistance, excellent mechanical properties, low shrinkage and stable color. Its composite material has excellent corrosion resistance, and the production size of BMC thermosetting plastics is precisely controllable, and it is widely used in the fields of electrical electronics, optical machinery, wind turbine blades, coatings, etc. However, existing BMC thermosetting plastics generally cannot be degraded and reused, and the environmental protection pressure is relatively large. Therefore, it is crucial to develop a degradable composite material that can be reused to achieve carbon neutrality benefits and reduce damage to the environment.
[0003] Chinese invention patent CN202110907016.0 discloses a high-performance degradable epoxy resin-carbon fiber composite material and its preparation method, wherein the carbon fiber surface is chemically treated and grafted with a thiol compound; the carbon fiber after being fully impregnated with epoxy resin and then laminated and compounded, a high-strength, degradable epoxy resin / carbon fiber composite material can be obtained. The composite material has high performance, high degradation efficiency and closed-loop recycling functions, but the cost of using carbon fiber cloth is relatively high. Chinese invention patent CN202210526287.6 discloses a degradable pultruded sheet composite material and its application in wind turbine blades. The composite material contains a degradable epoxy resin composition, a fiber raw material, a release agent and a filler. By optimizing the various formula components and proportions of the composition, a composite material is designed that can simultaneously meet the performance design requirements of the pultruded wind turbine blade main beam and has good degradability, but does not involve the recycling effect of the composite material after degradation. Summary of the invention
[0004] In order to develop a degradable composite material that can be reused to achieve carbon neutrality benefits and reduce damage to the environment, the first aspect of the present invention provides a degradable composite material, and the raw materials for preparing it include, by weight percentage: 20-50% of a degradable epoxy resin composition and 50-80% of raw material fiber.
[0005] As a preferred embodiment, the raw materials for preparing the degradable epoxy resin composition include, by weight: 60-80 parts of basic epoxy resin, 2.5-10 parts of modified degradable epoxy resin, and 20-40 parts of amine curing agent.
[0006] As a preferred embodiment, the modified degradable epoxy resin contains acetoacetate groups, and the glass transition temperature of the modified degradable epoxy resin is 120-130°C.
[0007] As a preferred embodiment, the modified biodegradable epoxy resin is EzCiclo epoxy resin sold by Shangwei New Materials Technology Co., Ltd.
[0008] As a preferred embodiment, the raw material fiber is selected from at least one of glass fiber, carbon fiber, basalt fiber, textile fiber, asbestos fiber and metal fiber.
[0009] As a preferred embodiment, the base epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, and alicyclic epoxy resin.
[0010] As a preferred embodiment, the amine curing agent includes but is not limited to aliphatic amine curing agents, aromatic amine curing agents, polyamide curing agents, and polyether amine curing agents.
[0011] As a preferred embodiment, the heating degradation temperature range of the degradable composite material is 80-200° C., and the heating degradation time is 1-48 hours.
[0012] As a preferred embodiment, the heating degradation temperature range of the degradable composite material is 80-180° C., and the heating degradation time is 1-48 hours.
[0013] The second aspect of the present invention provides an application of a degradable composite material in a BMC process.
[0014] As a preferred embodiment, the degradable composite material can be used to prepare, including but not limited to, automobile lampshades, helmets, sewer covers, battery box covers, tire racks, and cooling fans after being processed by the BMC process.
[0015] During the experiment, the applicant found that the modified degradable epoxy resin contained in the degradable epoxy resin composition can make the degradable composite material have good degradability. The possible reason is speculated that the degradable epoxy resin composition contains a modified degradable epoxy resin, in which the acetoacetate group contained is combined with the base resin through a chemical reaction, and it can achieve degradation performance through mechanochemical activation and reaction with the degradation liquid, degrade into oligomers, and has excellent mechanical properties.
[0016] The applicant discovered during the experiment that after the degradable composite material is degraded, it is pre-reacted with a monofunctional epoxy diluent to obtain a modified fiber raw material. The modified fiber raw material is combined with an epoxy resin to obtain a degradable composite material that can be used in the processing technology of bulk molding compounds. The possible reason is that the fibers separated from the prepared degradable composite material can be pre-reacted and put back into use, and the fibers in the degradable composite material will not degrade in the degradation liquid, and still have good strength properties after being used again.
[0017] As a preferred embodiment, the method for preparing the degradable composite material comprises the following steps:
[0018] The basic epoxy resin, the modified degradable epoxy resin, the amine curing agent and the raw material fiber are mixed and then the degradable composite material is obtained according to the material forming process of hand lay-up, molding and infusion. The curing time is 4-12 hours and the curing temperature is 40-120°C.
[0019] As a preferred embodiment, the molding process includes but is not limited to hand lay-up, molding, infusion, etc.
[0020] As a preferred embodiment, the specific steps of the degradable composite material in the BMC process are as follows:
[0021] S1 cuts the degradable composite material, and then places the degradable composite material in a degradation liquid for heating and degradation to separate fibers;
[0022] S2: the fiber is spun dry and then washed to calculate the mass of the residual degradation liquid, and the fiber is pre-reacted;
[0023] S3: putting the pre-reacted fiber into a kneading machine, then introducing the epoxy material required for the BMC parts, and starting the kneading machine to completely wet the epoxy material and the fiber;
[0024] S4 takes out the kneaded dough and then puts it into a mold for compression molding and curing.
[0025] As a preferred embodiment, the cutting size of the degradable composite material is 3-8 cm in length, 3-8 cm in width, and 0-3 cm in thickness but not 0 cm.
[0026] As a preferred embodiment, the degradation liquid is CleaVER-H degradation liquid sold by Swank New Materials Technology Co., Ltd.
[0027] As a preferred embodiment, the monofunctional epoxy diluent is selected from alkylene glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C 12-14At least one of aliphatic glycidyl ether, benzyl glycidyl ether and o-cresyl glycidyl ether.
[0028] As a preferred implementation, the epoxy material in step S3 includes epoxy resin and silicon powder.
[0029] As a preferred embodiment, in terms of weight percentage, the fibers separated after degradation in step S2 account for 15-25%, the epoxy resin accounts for 40-55%, and the silicon powder accounts for 20-40%.
[0030] As a preferred embodiment, the length of the fibers separated after degradation in step S2 is 1-5 cm.
[0031] As a preferred implementation, the kneading time in step S3 is 10-60 min, and the kneading speed is 100-800 r / min.
[0032] As a preferred embodiment, the curing temperature of the compression molding in step S4 is 120-180° C., and the curing time of the compression molding is 10-30 min.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The degradable composite material of the present invention, the modified degradable epoxy resin contained in the degradable epoxy resin composition can make the degradable composite material have good degradability.
[0035] (2) The degradable composite material of the present invention is degraded and then pre-reacted with a monofunctional epoxy diluent to obtain a modified fiber raw material. The modified fiber raw material is combined with an epoxy resin to obtain a degradable composite material that can be applied to the processing technology of bulk molding compounds.
[0036] (3) The degradable composite material of the present invention is applied to the BMC process, and the degraded fibers of the degradable composite material are used. The degraded fibers can be reused after pre-reaction without changing other processes.
[0037] (4) The degradable composite material of the present invention is applied to the BMC process, and the fibers after degradation of the degradable composite material realize a closed loop of recycling and application of the degradable composite material.
[0038] (5) The degradable composite material of the present invention is applied to the BMC process. The fibers of the composite material can be recycled and reused after degradation, which can effectively avoid the impact of post-processing of the composite material on the environment. DETAILED DESCRIPTION
[0039] The basic epoxy resin, raw material fiber and amine curing agent are all conventionally available on the market.
[0040] Example 1
[0041] A degradable composite material, the raw materials for preparation of which include, by weight percentage, 50% of a degradable epoxy resin composition and 50% of raw material fiber.
[0042] The raw materials for preparing the degradable epoxy resin composition include, by weight: 70 parts of basic epoxy resin, 7.5 parts of modified degradable epoxy resin, and 30 parts of amine curing agent.
[0043] The basic epoxy resin is bisphenol A epoxy resin purchased from Yangnong Hengrui New Materials Technology Co., Ltd., model number YN1828.
[0044] The modified degradable epoxy resin was purchased from Shangwei New Materials Technology Co., Ltd. and its model is EzCiclo epoxy resin.
[0045] The amine curing agent is diethylenetriamine.
[0046] The raw material fiber is glass fiber.
[0047] A method for preparing a degradable composite material comprises the following steps:
[0048] The basic epoxy resin, the modified degradable epoxy resin, the amine curing agent and the raw material fiber are mixed and then the degradable composite material is obtained according to the vacuum infusion material molding process. The curing time is 11-12 hours and the curing temperature is 80-100°C.
[0049] The application of a degradable composite material in the BMC process includes the following specific steps:
[0050] S1 cuts the degradable composite material, and then places the degradable composite material in a degradation liquid for heating and degradation to separate fibers;
[0051] S2: the fiber is spun dry and then washed to calculate the mass of the residual degradation liquid, and the fiber is pre-reacted;
[0052] S3: putting the pre-reacted fiber into a kneading machine, then introducing the epoxy material required for the BMC parts, and starting the kneading machine to completely wet the epoxy material and the fiber;
[0053] S4 takes out the kneaded dough and then puts it into a mold for compression molding and curing.
[0054] The cutting dimensions of the degradable composite material are 5 cm in length, 5 cm in width and 2 cm in thickness.
[0055] The degradation liquid is CleaVER-H degradation liquid sold by Swanwell New Materials Technology Co., Ltd.
[0056] The monofunctional epoxy diluent is alkylene glycidyl ether.
[0057] The epoxy material in step S3 includes epoxy resin and silicon powder.
[0058] In terms of weight percentage, the fiber separated after degradation in step S2 accounts for 22%, the epoxy resin accounts for 54%, and the silicon powder accounts for 24%.
[0059] The epoxy resin is Nan Ya 128.
[0060] The length of the fiber separated after degradation in step S2 is 1 cm.
[0061] The kneading time in step S3 is 60 min, and the kneading speed is 450 r / min.
[0062] The compression molding curing temperature in step S4 is 150° C., and the compression molding curing time is 20 minutes.
[0063] Example 2
[0064] The raw materials and preparation method of a degradable composite material are the same as those in Example 1. The application of a degradable composite material in a BMC process, and the specific application steps are the same as those in Example 1, except that the length of the fiber separated after degradation in step S2 is 2 cm.
[0065] Example 3
[0066] The raw materials and preparation method of a degradable composite material are the same as those in Example 1. The application of a degradable composite material in a BMC process, and the specific application steps are the same as those in Example 1, except that the length of the fiber separated after degradation in step S2 is 3 cm.
[0067] Example 4
[0068] The raw materials and preparation method of a degradable composite material are the same as those in Example 3. The application of a degradable composite material in a BMC process, and the specific application steps are the same as those in Example 1, except that, in terms of weight percentage, the fiber separated after degradation in step S2 is 16.2%, the epoxy resin is 43.8%, and the silicon powder is 40%.
[0069] Example 5
[0070] The raw materials and preparation method of a degradable composite material are the same as those in Example 4. The application of a degradable composite material in a BMC process, and the specific application steps are the same as those in Example 1, except that the length of the fiber separated after degradation in step S2 is 5 cm.
[0071] Comparative Example 1
[0072] A degradable composite material is used in a BMC process. The specific application steps are the same as those in Example 1, except that commercially available conventional fibers are used in step S2. The fibers are glass fiber 800g axial cloth with a fiber length of 3cm.
[0073] Comparative Example 2
[0074] A degradable composite material is used in a BMC process. The specific application steps are the same as those in Example 1, except that commercially available conventional fibers are used in step S2. The fibers are glass fiber 800g axial cloth with a fiber length of 5cm.
[0075] Performance Testing
[0076] In the BMC process step S4, the kneaded mass is taken out and then placed in a plate mold for compression molding and curing to prepare a plate for performance testing. The flexural strength, flexural modulus, and flexural strain test methods are ISO178, and the tensile stress and tensile modulus test methods are ISO527-2, 1B type specimens. The performance test methods are as follows:
[0077] The test results are shown in Table 1 below.
[0078] Table 1
[0079]
[0080] Combining Examples 4 and 5 with Comparative Examples 1 and 2, it can be seen that the BMC board made by using degraded fibers from the degradable composite material to replace the commonly used fibers on the market can achieve a strength retention rate of more than 85%, which means that the fibers in the degradable composite material board can be degraded and recycled by this method and reused.
Claims
1. A degradable composite material, characterized in that: The raw materials for preparation include, by weight percentage: 20-50% of degradable epoxy resin composition and 50-80% of raw material fiber.
2. The degradable composite material according to claim 1, characterized in that: The raw materials for preparing the degradable epoxy resin composition include, by weight: 60-80 parts of basic epoxy resin, 2.5-10 parts of modified degradable epoxy resin, and 20-40 parts of amine curing agent.
3. The degradable composite material according to claim 2, characterized in that: The modified degradable epoxy resin contains acetoacetate groups, and the glass transition temperature of the modified degradable epoxy resin is 120-130°C.
4. The degradable composite material according to claim 1, characterized in that: The raw material fiber is selected from at least one of glass fiber, carbon fiber, basalt fiber, fabric fiber, asbestos fiber and metal fiber.
5. The degradable composite material according to claim 2, characterized in that: The basic epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin and alicyclic epoxy resin.
6. The degradable composite material according to claim 1, characterized in that: The heating degradation temperature range of the degradable composite material is 80-200° C., and the heating degradation time is 1-48 hours.
7. Use of the degradable composite material according to any one of claims 1 to 6 in a BMC process.
8. The use of the degradable composite material in the BMC process according to claim 7, characterized in that: The specific steps of the BMC process are as follows: S1 cuts the degradable composite material, and then places the degradable composite material in a degradation liquid for heating and degradation to separate fibers; S2: the fiber is spun dry and then washed to calculate the mass of the residual degradation liquid, and the fiber is pre-reacted; S3: putting the pre-reacted fiber into a kneading machine, then introducing the epoxy material required for the BMC parts, and starting the kneading machine to completely wet the epoxy material and the fiber; S4 takes out the kneaded dough and then puts it into a mold for compression molding and curing.
9. The use of the degradable composite material in the BMC process according to claim 8, characterized in that: The kneading time in step S3 is 10-60 min, and the kneading speed is 100-800 r / min.
10. The use of the degradable composite material in the BMC process according to claim 8, characterized in that: The curing temperature of the compression molding in step S4 is 120-180° C., and the curing time of the compression molding is 10-30 minutes.
Citation Information
Patent Citations
Degradable pultrusion plate composite material and application thereof on wind power blade
CN114891317A
A high-performance biodegradable epoxy resin-carbon fiber composite material and preparation method thereof
CN115703892B